2019
DOI: 10.1111/imj.14141
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour change techniques to optimise participation in physical activity or exercise in adolescents and young adults with chronic cardiorespiratory conditions: a systematic review

Abstract: Participation in regular physical activity decreases the risk of developing cardiometabolic disease. However, the proportion of people who participate in the recommended amount of physical activity is low, with common barriers including competing interests and inclement weather. In people with chronic cardiorespiratory conditions, participation in physical activity is reduced further by disease‐specific barriers, time burden of treatment and unpleasant symptoms during physical activity. Addressing these barrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 56 publications
0
5
0
1
Order By: Relevance
“…34 In addition, a planning schedule of exercises, developed by therapists, patients, and family members, associated with diaries reporting difficulties and challenges may help to monitor adaptations and progression of exercises. 35,36 Overall, the findings of this study suggest that prescription of general and respiratory exercises to patients with CF should be accompanied by strategies to monitor adherence to treatment. Non-monitoring may result in amounts of exercise inferior to those recommended.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…34 In addition, a planning schedule of exercises, developed by therapists, patients, and family members, associated with diaries reporting difficulties and challenges may help to monitor adaptations and progression of exercises. 35,36 Overall, the findings of this study suggest that prescription of general and respiratory exercises to patients with CF should be accompanied by strategies to monitor adherence to treatment. Non-monitoring may result in amounts of exercise inferior to those recommended.…”
Section: Discussionmentioning
confidence: 80%
“…Health education, for instance, has proved to be effective for improving pain, disability, mental and physical health‐related quality‐of‐life in individuals with chronic low back pain 34 . In addition, a planning schedule of exercises, developed by therapists, patients, and family members, associated with diaries reporting difficulties and challenges may help to monitor adaptations and progression of exercises 35,36 . Overall, the findings of this study suggest that prescription of general and respiratory exercises to patients with CF should be accompanied by strategies to monitor adherence to treatment.…”
Section: Discussionmentioning
confidence: 94%
“…Our review of the literature identified several BCTs (beyond goal setting and self-monitoring) that are commonly used in behavior change interventions (including mobile-based ones) designed for adolescents [19,49,50], including social support [34,51], prompts or cues [52][53][54][55], modeling [34], providing consequences for behavior [34,51], and feedback on behavior [51]. However, few studies have investigated their efficacy in actually changing health behaviors among adolescents.…”
Section: Effective Bcts Among Adolescentsmentioning
confidence: 99%
“…Quadro 2. Técnicas de mudança comportamental identificadas (adaptado de Behavior Change Technique Taxonomy (V1), de Michie, Atkins & West, 2014) 5,13,20,23,24,26,27,30,33,45,51 Vários estudos mostram que, a implementação de técnicas de mudança comportamental tem sido eficaz na gestão da doença crónica (Sawyer et al, 2019;Duff et al, 2017 (Marra et al, 2019;Hung et al, 2016;Koniak-Griffin et al, 2015;Kempf et al, 2017). Alguns estudos têm vido mostrar que as ferramentas digitais têm contribuído não apenas para auto-gestão da doença crónica, como também reduzir as desigualdades em termos de acessibilidade aos serviços de saúde (Wade & Stocks, 2017).…”
Section: Resultsunclassified